GEOCHEMICAL CHARACTERISTICS OF THE ACCUMULATION OF RARE AND SCATTERED ELEMENTS IN THE BRECCIAS OF MUD VOLCANOES OF AZERBAIJAN (ABSHERON PENINSULA, GOBUSTAN) - Babayev, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Based on modern field and laboratory studies, the conditions for the accumulation of some rare and scattered elements in mud volcano breccias have been described in the article, using the example of the most characteristic mud volcanoes of Absheron and Gobustan. A typomorphic geochemical association with boron mineralization of rare and scattered elements in solid products of mud volcanic eruptions has been determined. It has been revealed that mud volcanism is a favorable factor for the accumulation of boron, lithium, cesium and strontium in mud volcano breccias in practically interesting values. The maximum values of these concentrations were noted in the fresh erupted mud volcano breccias with remnants of water-silty mud. Sample variance, standard deviation, and coefficient of variation are the most controlling parameters of the distribution functions of the studied elements in mud volcano breccias. According to the estimates of these parameters, it has been found that the mud volcanic new formations are rich in boron, lithium and cesium, while not being rich in rubidium. The established average values of the concentration of boron (0.216 kg/t), lithium (55 g/t), rubidium (132 g/t) and cesium (50 g/t) can be considered as the first quantitative parameters of the geochemical specialization of mud volcanic eruption products using the example of Absheron Peninsula and Gobustan. These parameters can be used to refine the so-called provincial clarkes of geochemical zoning, prediction of prospecting for boron and rare alkalic, and other problems.
Keywords: mud volcano; breccia; rare elements; mineralization; clarke; concentration; boron; alkaline elements; spectral analysis